Haiti : Financial System Stability Assessment, including a Report on the Observance of Standards and Codes on Banking Supervision. (IMF Staff Country Reports; Country Report, 2008)
Haiti's financial system plays a limited role in supporting economic growth. The Financial Sector Assessment Program (FSAP) team assessed that financial sector data are generally adequate, although the unavailability of some statistics has weakened the analysis. Stress tests suggest that the banking system is resilient to a range of single-risk factor shocks, but would be vulnerable to a deterioration in credit quality. The banking sector needs to play a more effective role in supporting growth. There is no explicit law governing payment systems.